A aptidão física está comprometida na neurofibromatose tipo 1, mesmo nas formas de menos gravidade - Juliana Ferreira de Souza (2012)
Background: Neurofibromatosis type 1 (NF1) is a genetic autosomal dominant disease characterized by neurocutaneous signs but also a multisystem disorder with a wide variety of clinical manifestations and different levels of severity. It has been observed that individuals with NF1 have reduced handgrip force, shorter life expectancy and quality of life, more frequent and earlier cardiovascular involvement than the general population as well as decreased aerobic capacity. Fine motor coordination deficits and poorer motor proficiency have also been demonstrated in individuals with NF1. Physical fitness is a set of attributes related to the ability to perform physical activity. The health-related physical fitness is determined by aerobic capacity, body composition, and musculoskeletal constitution (flexibility, muscular strength and endurance). We hypothesised that physical fitness is impaired in individuals with NF1. Objective: To evaluate if individuals with NF1 have decreased physical fitness compared with unaffected controls matched by sex and age. Patients and Methods: A sample of 22 patients attended at the Neurofibromatosis Outpatient Reference Center was matched by age and sex to 22 unaffected volunteers and evaluated for: anthropometry, body composition, distance covered in 6 minutes walk test (6MWT), lung function (spirometry), respiratory muscle strength (maximum inspiratory and expiratory pressure), maximal handgrip force, habitual levels of physical activity, cardiac function and myocardial mass (echocardiography). Results: Individuals with NF1 presented lower body mass index (BMI) and lower fat percentage than controls. We also observed shorter distance on the 6MWT, reduced handgrip force and respiratory muscle strength among individuals with the disease. Spirometry showed respiratory function was not different in both groups. Echocardiography showed similar myocardial mass and normal cardiac function in comparing individuals with NF1 and their controls. Conclusion: Individuals with NF1 presented with reduced physical fitness (shorter distance on the 6MWT, reduced Fmax and respiratory muscle strength) than unaffected controls. All together, this study results show physical fitness impairment which represents poorer performance in carrying out daily activities among individuals with NF1.